PENGEMBANGAN MODUL AJAR BAHASA INDONESIA BERBASIS ETNOLINGUISTIK PADA MATERI IDE POKOK SEBUAH PARAGRAF DI KELAS IV SEKOLAH DASAR - Isra Miranti Septia; Muhammadi; Elfia Sukma; Adrias (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study was motivated by the lack of contextual teaching materials in Indonesian language instruction, particularly regarding the main idea of a paragraph in fourth-grade elementary school, which causes students to struggle with understanding the content of reading passages. This study was conducted in fourth-grade classes at SD Negeri 03 Bandar Buat, SD Negeri 16 Pagambiran, and SD Negeri 35 Pagambiran. The objective of this study is to produce a valid, practical, and effective ethnolinguistics-based Indonesian language teaching module capable of improving students’ learning outcomes in identifying the main idea of a paragraph. The research design employed is a Research and Development (R&D) study using the 4D model, which includes the Define, Design, Develop, and Disseminate stages. The developed teaching module was validated by subject matter experts, media experts, and language experts using a validation sheet. The practicality test was conducted through teacher and student response questionnaires, while the effectiveness test was conducted through pre-tests and post-tests analyzed using N-Gain. The results of the study indicate that the teaching module achieved a validity level of 93.69%, categorized as highly valid, , practicality of 95.83% among teachers and approximately 97% among students in the “very practical” category, as well as effectiveness with an N -Gain at the pilot school, SD Negeri 03 Bandar Buat, was 89.52%, at the first implementation school, SD Negeri 16 Pagambiran, 93.45%, and at the second implementation school, SD Negeri 35 Pagambiran, 95.54%; all three schools fell into the effective category. Thus, the ethnolinguistics-based teaching module is deemed valid, practical, and effective for use in Indonesian language instruction.